The surgical restoration of arm and hand function in tetraplegic patients - Harhaus-Wähner, Leila; Aman, Martin; Pennekamp, Anna; Weidner, Norbert; Panzram, Benjamin; Gohritz, Andreas (Deutsches Ärzteblatt, 2023)
Background: There are approximately 140 000 people in Germany with spinal cord injury, with approximately 2400 new patients each year. Cervical spinal cord injuries cause, to varying degrees, weakness and impairment of everyday activities of the limbs (tetraparesis, tetraplegia). - Methods: This review is based on relevant publications retrieved by a selective search of the literature. - Results: From among 330 initially screened publications, 40 were included and analyzed. Muscle and tendon transfers, tenodeses, and joint stabilizations yielded reliable functional improvement of the upper limb. Tendon transfers improved the strength of elbow extension from M0 to an average of M3.3 (BMRC) and grip strength to approximately 2 kg. In the long term, 17-20% of strength is lost after active tendon transfers and slightly more after passive ones. Nerve transfers improved strength to M3 or M4 in over 80% of cases, with the best results overall in patients under 25 years of age who underwent early surgery (within 6 months of the accident). Combined procedures in a single operation have been found to be advantageous compared to the traditional multistep approach. Nerve transfers from intact fascicles at segmental levels above that of the spinal cord lesion have been found to be a valuable addition to the established varieties of muscle and tendon transfer. The reported long-term patient satisfaction is generally high. - Conclusion: Modern techniques of hand surgery can help suitably selected tetraparetic and tetraplegic patients regain the use of their upper limbs. Competent interdisciplinary counseling about these surgical options should be offered as early as possible to all affected persons as an integral part of their treatment plan.